2013
DOI: 10.1089/cap.2013.0050
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and Cardiometabolic Safety of Clozapine in the Treatment of Very Early Onset Schizophrenia: A Retrospective Chart Review

Abstract: It appears that clozapine use in very early onset schizophrenia is safe. Although hematological adverse effects did occur in our study, the rates were not much higher than those seen in the control group. We found that the hematological abnormalities in the CTG were mostly transient, and that treatment with clozapine can be safely continued or renewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… 80% female (n = 40), 20% males (n = 10) Inpatient psychiatry service of a general paediatric hospital in North East USA, all receiving treatment for a suicide plan or attempt Not reported Not reported Not reported RCT Tobacco Use, Alcohol Use High rates of tobacco use in a sample of young people receiving treatment for suicidal ideation/attempts. Midbari et al, (2013) [ 52 ] Israel Young people under 13 years hospitalized in a psychiatric ward treated with clozapine or other psychoactive medication 36 Clozapine: 10.4 (2 sd. ); Non-Clozapine 10.1 (1.4 sd.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 80% female (n = 40), 20% males (n = 10) Inpatient psychiatry service of a general paediatric hospital in North East USA, all receiving treatment for a suicide plan or attempt Not reported Not reported Not reported RCT Tobacco Use, Alcohol Use High rates of tobacco use in a sample of young people receiving treatment for suicidal ideation/attempts. Midbari et al, (2013) [ 52 ] Israel Young people under 13 years hospitalized in a psychiatric ward treated with clozapine or other psychoactive medication 36 Clozapine: 10.4 (2 sd. ); Non-Clozapine 10.1 (1.4 sd.)…”
Section: Resultsmentioning
confidence: 99%
“…Non-fasted lipid and blood related biomarkers were reported across nine studies. Triglycerides were the most commonly reported [ 18 , 19 , 33 , 40 , 44 , 52 , 56 ]. Weighted average triglycerides were 97.7 mg/dL (95% CI 62.26–128.14; N = 161), and pooled prevalence rate of elevated triglycerides was 23.1% (95% CI 9.2–47.3; N = 193).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the severe psychiatric disorders supporting clozapine, early-onset schizophrenia (EOS) is a rare form of schizophrenia de ned by an onset before the age of 18 with a prevalence < 1/10 000 children in the general population (50).Two systematic reviews of the literature (5,6), have shown the superior e cacy of clozapine in resistant EOS.…”
Section: Discussionmentioning
confidence: 99%